Extraction, reimmobilization and characterization of spent immobilized lipase - Mokhtar, Nur Fathiah (2020)
Currently, lipases are considered as one of the important catalysts in substituting the use of chemical reactions in a wide variety of processes. In 2015, the report estimated that the U.S. enzyme's market had a high demand for processed foods and synthesis reactions, which generated more than USD 1 billion in sales. However, the reusability of the industrial immobilized lipase was limited only after several cycles of reactions. After that, the spent immobilized lipase will be replaced with the new immobilized lipase. The inability to reuse the spent immobilized lipase leads to an increased cost required for the new uptake of the enzyme. Practically in industry, the spent immobilized lipase is a waste from industrial users. The spent immobilized lipase still has potential use even though the activity was lower than the new immobilized lipase. There was no study done on the extraction and reimmobilization of the enzyme from the spent immobilized lipase. Therefore, the objective of this research is to study the feasibility of the spent lipase to be extracted, reimmobilized, and characterized. General methodology involved the recovery of the spent immobilized lipase via chemical and mechanical extraction. The chemical extraction approach via Reverse Micelles Extraction (RME) showed the highest lipase recovery, which was 66% compared to the 34% of lipase yield obtained from the mechanical extraction method. The extracted lipase was reimmobilized via simple adsorption into the ethanol pretreated carrier. The characterization of the reimmobilized lipase at different pH and temperature was conducted. The optimum conditions of immobilization resulted in 96% of the extracted lipase being immobilized. The reimmobilized lipase optimum activity was at 50°C and pH 6. The reimmobilized lipase was incubated for 20 h in pH 6 buffer at 50°C of water bath shaker. The reimmobilized lipase still had 27% residual activity after 18 h of incubation, which indicated higher thermal stability compared to the free lipase. The Scanning Electron Microscope (SEM) was used to study the morphology of the reimmobilized lipase. The morphological of immobilized lipase was analyzed based on the pore and the particle sizes of the support. SEM also showed oil on the surface of immobilized lipase before and after the solvent treatment. The structural analysis of free lipase and reimmobilized lipase was determined by Fourier-transform infrared spectroscopy (FTIR). The structures of the amide group I (CO stretch) and amide group II (NH bend), which formed the functional group of the free commercial lipase, extracted lipase and reimmobilized lipase, had been identified. In conclusion, the free lipase was successfully extracted from the spent immobilized lipase and reimmobilized into Accurel MP1008 carrier. It exhibited high thermal stability, and the reusability of the spent enzyme will promote continued use of industrial lipase and reduce the cost of the manufacturing process.